APLIKASI BERBAGAI KONSENTRASI ASAP CAIR ENCER DARI LIMBAH INDUSTRI KERAJINAN KAYU TERHADAP AROMA DAN CITA RASA DAGING SEI - Max A.J. Supit; Ludia Gasong; Bachtaruddin Badewi (Partner, 2010)
Application of Various Concentrations of Woodcarving Waste Liquid Smoke on Sei Meat Aroma and Flavour. Utilization of waste from woodworking industry to produce liquid smoke (LS) and application of the LS is a new method in sei meat production. This experiment was aimed to find proper concentration of the LS to produce sei meat that replicate a selected traditionally-produced sei meat. A Difference-From-Control-Test was used to obtain mean of differences of 4 treatments namely blind control; A0-without LS; A1-1% LS; A2-2% LS, and A3-3% LS. Data analysis results (ANOVA) showed that all treatments that contain LS were different from blind control. The differences may be due to the use of different kind of woods to produce LS and/or by the differences in LS concentration applied.Keyword : waste from woodworking industry, liquid smoke, sei meat (smoked meat)